eHealth literacy and attitudes towards use of artificial intelligence among university students in the United Arab Emirates, a cross-sectional study - Alam, Zufishan; Abdullahi, Aminu S.; Alnuaimi, Shamma Nayea Salem; Al Shaka, Hanouf Abubaker; Alderei, Saif Slayem Saif; Alhemeiri, Ahmed Abdulla Ali; Khorzom, Hayma; Almaskari, Hamad Jumaa Mubarak; Almaamari, Khalid Abdulrahman; Al seiari, Khalifa; Al Saadi, Mohammed; Al Shamsi, Nasser; et al. (Frontiers in Digital Health, 2025)
IntroductionWith the rapid digitalization of healthcare information and the increasing dependability on online health resources, it has become crucial to understand digital health literacy and the use of emerging AI technologies like ChatGPT among stakeholders. This is of particular importance in the United Arab Emirates which has the highest internet penetration rates.MethodThis study aimed to assess eHealth literacy and the factors influencing it among university students in the United Arab Emirates. Their attitudes towards ChatGPT use were also explored. Data from participants, studying in the public universities of UAE, was collected between April–July 2024 using eHEALS and TAME Chat GPT instruments.ResultsResults indicated a mean eHealth literacy score of 29.3 out of 40, with higher scores among females and those in health–related disciplines. It was also found that students with higher eHealth literacy perceived ChatGPT as more useful in healthcare, despite their concerns about its risks and potential to replace healthcare professionals.DiscussionThe findings from the study underscore the need of development of tailored digital health curricula, to enhance eHealth literacy particularly in subgroups showing lower literacy scores. Moreover, it is also imperative to develop guidelines for responsible and ethical AI use in health information seeking.